Trophic Status Monitoring for the Bangka Strait in Indonesia during the COVID-19 Period Using MODIS Data - Susanti, Susi; Rendana, Muhammad; Novia, Novia; Bahrin, David (Indonesian Journal of Environmental Management and Sustainability, 2024)
Many surface waters in the world are impounded by eutrophication due to the global warming phenomenon. This study analyzed the trophic level in the Bangka Strait, a busy pathway that connects two provinces (Bangka and South Sumatra) of Indonesia, using MODIS-Terra chlorophyll-a (Chl-a) data from the 2020 year. We applied the GIS analysis to generate Chl-a concentration and trophic state maps over the study area. The results of the study revealed that the mesotrophic, eutrophic, and oligotrophic status encompass 50%, 43%, and 7% of the Bangka Strait region, respectively. The highest concentration of Chl-a was observed in May (5.38 g/L), while the lowest was observed in September (3.02 g/L). Our study revealed that the high Chl-a concentration was primarily due to nutrient contributions from South Sumatra rivers. On the other hand, the COVID-19 restriction policy significantly reduced Chl-a from July to October. The trophic state of the Bangka Strait was at a mesotrophic level, and the major contributors to the trophic condition in the strait came from the coasts of South Sumatra, which mostly consisted of agricultural and aquacultural activities. These findings will be useful in developing an effective policy for monitoring and protecting surface waters from eutrophication events.